Differentiation of expenditure on health and life insurance in households in 2006–2020 - Wicka, Aleksandra; Wicki, Ludwik (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Along with the growing wealth of society, the demand for insurance, including health insurance, increases. In recent years, there has been significant interest in insurance products which guarantee access to private healthcare facilities. The waiting time for an appointment with a specialist is shorter than in public institutions, and such insurance offers quick diagnostics and high-quality services. The study aimed to determine the level and differentiation of health insurance expenditure in various types of households and its share in total insurance expenses. From 2006 to 2020, as shown by statistics, the highest expenditure on health insurance was recorded in the households of non-manual workers (PLN 19.72 per person per year on average) and the lowest — in farmers’ families (8.85 per person per year on average). The indicator of the diversification of insurance expenditure structures for the surveyed households calculated for 2020 showed that farmers’ households had a significantly different (various) structure of expenditure on insurance than that observed in other types of households (total v pq = 0.96).
Keywords: health insurance; households; insurance expenditure